MENATA KAWASAN DENGAN PENDEKATAN KONSEP SHARING CITY - Putri, Nyssa Iga; Ellisa, Evawani (RUSTIC, 2024)
This research is driven by the inquiry: how does the ancient practice of sharing adapt as a cultural norm in contemporary urban environments? Focusing on the Kalimalang area in Bekasi, which was initially designated as a protected zone due to the presence of the Kalimalang canal, the study traces its evolution into a densely populated region, catalyzed by rapid transportation advancements such as the Indonesia-China High-Speed Rail (KCIC) and LRT Line 2. Through comprehensive analysis spanning macro, mezzo, and micro scales, the study investigates the feasibility of integrating the sharing city principle into urban revitalization endeavors for Kalimalang. Employing data triangulation techniques, informed by insights from "Sharing Cities: A Case for Truly Smart and Sustainable Cities" by McLaren & Agyeman, the research proposes urban design strategies tailored to the northern Kalimalang area. Ultimately, the study asserts that embracing the sharing city concept offers a promising avenue to address the area's challenges amidst unchecked urban expansion, advocating for further exploration of public-private space distribution and emphasizing stakeholder engagement for collaborative, sustainable progress in the Kalimalang environment.